Review Article: Vitamin’s D Physiologic Properties and Functions - AL-anbagi, Lamiaa Saoud Abbod; Hussaein, Rafah Oday (Journal for Research in Applied Sciences and Biotechnology, 2023)
When 7-dehydrocholesterol is exposed to ultraviolet light, a prohormone called In the skin D3 is created. Being biologically inert, it must first be changed into 25-hydroxyvitamin D. D3 must first be converted to 1,25-dihydroxyvitamin D3 in the kidney formerly usage. The 1,25-dihydroxyvitamin D3 hormone, which has an array of functions, interacts with a nuclear receptor, includes calcium concentration, intestinal phosphate concentration, and bone calcium mobilization, and kidney calcium reabsorption. There are numerous additional noncalcemic uses for it in the body. In this review, physiological, endocrinologic, and molecular biologic properties of vitamin D are briefly discussed.